The question of representation in Elizabethan literature. - Wilson, Timothy H. (University of Ottawa (Canada), 1998)
The sixteenth century has become a focal point for the analysis of the genealogy of political imperialism. It marks the shift from the medieval to the modern age as manifested in the discovery of the New World, the rise of imperial control and expansion, and the historical construction of the individual subject. My dissertation argues that Sidney, Spenser, and Shakespeare, to some extent, all participate in the "imperial" disposition of modern representational thinking. However, all three authors also offer alternatives to imperial and representational thinking. The first chapter uses Heidegger's conception of the work of art in order to assert that art is not always and only a representational copy of an original. For Heidegger, the work of art is not an imitation of a pre-existing thing, nor is it an epiphenomenon of a system of relations. On the contrary, it first founds these relations. The second chapter analyzes the conception of poiesis which Sidney presents in his Defence of Poesie. In some respects, Sidney's definition is merely a reformulation of the representational one. That is, for Sidney poetry imitates the ideal rather than "brasen" nature. However, in other respects, insofar as he draws on certain formulations of the Italian humanists, Sidney conceives of poiesis as a figuring forth of something for the first time. In the third chapter, I turn to Book I of Spenser's The Faerie Queene. This chapter takes issue with contemporary readings of Spenser which assert that he is our "preeminent poet of empire." I point out that the entire conception of the just and true order of things that is presented in Book I speaks against the assertion of an imperial disposition in Spenser. Finally, in the fourth chapter, I deal with Shakespeare's Hamlet in relation to the Cartesian metaphysics of the subject. In modern metaphysics, the sovereign subject becomes master over existence. I demonstrate the ways in which "The Mouse-trap" figures forth this imperial control over nature that the subject wields. However, I also explore the ways in which it presents a non-representational experience of truth along the lines of the pre-metaphysical experience of a-letheia.
Keywords: Theater.